OPPORTUNITIES FOR ADAPTING ISLAMIC BANKING PRODUCTS TO THE RUSSIAN LEGISLATIVE FRAMEWORK - V. Malyaev (BRICS Law Journal, 2017)
In countries with a large Muslim population who are not willing to trust their savings to traditional banks, as well as a significant number of Muslim entrepreneurs who are not using the services of traditional banks, the creation of Islamic financial institutions can improve the efficiency of the financial market and accelerate its development. Russia is one of these countries. Islamic financial products can attract both Russian companies as well as traditional companies oriented to the observance of the Quran. While Russian legislation does not provide opportunities for the application of Islamic financial products, the issues of adaptation and the possibility of realising these projects in Russia are becoming very relevant. The aim of this paper is to present the results of a study devoted to the analysis of possibilities of the application of Islamic financial products in Russia.